2011
DOI: 10.4166/kjg.2011.57.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Sustained Virologic Response in Chronic Hepatitis C: Analysis of Factors Related to Relapse after Sustained Virologic Response with Peginterferon Plus Ribavirin Combination Therapy

Abstract: Background/Aims: Pegylated interferon plus ribavirin combination therapy has been the standard of therapy for patients with chronic hepatitis C. Although previous studies have reported long term durability after the sustained virologic response (SVR) with standard therapy for chronic hepatitis C, it is still unclear in Korea. The aim of this study was to evaluate the relapse rate and related factors after SVR to pegylated interferon therapy in Korean patients with chronic hepatitis C. Methods: A total of 119 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In some studies, on the other hand, higher sustained viral response was received from patients with high viral load (> 850,000 IU/mL) compared to those with low viral load (9,(18)(19)(20)(21) In a study performed on recurrence after treatment, HCV RNA was determined in 7 (2%) patients out of 400, 5 of them were followed-up, and HCV RNA was found again in 2 patients (0.5%) 12 months after the treatment (24). On the other hand, there are studies in which late recurrence rates were high: Lee JE et al (25), Reichard et al (26), and Khokhar et al (27) reported the rates as 7.4%, 8%, and 8.8%, respectively. These inconsistencies result from PCR methods used in varying sensitivity and patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, on the other hand, higher sustained viral response was received from patients with high viral load (> 850,000 IU/mL) compared to those with low viral load (9,(18)(19)(20)(21) In a study performed on recurrence after treatment, HCV RNA was determined in 7 (2%) patients out of 400, 5 of them were followed-up, and HCV RNA was found again in 2 patients (0.5%) 12 months after the treatment (24). On the other hand, there are studies in which late recurrence rates were high: Lee JE et al (25), Reichard et al (26), and Khokhar et al (27) reported the rates as 7.4%, 8%, and 8.8%, respectively. These inconsistencies result from PCR methods used in varying sensitivity and patient populations.…”
Section: Discussionmentioning
confidence: 99%